Global changes in maternity care provision during the COVID-19 pandemic: A systematic review and meta-analysis. (July 2021) - Townsend, Rosemary; Chmielewska, Barbara; Barratt, Imogen; Kalafat, Erkan; van der Meulen, Jan; Gurol-Urganci, Ipek; O'Brien, Pat; Morris, Edward; Draycott, Tim; Thangaratinam, Shakila; Doare, Kirsty Le; Ladhani, Shamez; et al.
Abstract: Background: The COVID-19 pandemic has had a profound impact on healthcare systems globally, with a worrying increase in adverse maternal and foetal outcomes. We aimed to assess the changes in maternity healthcare provision and healthcare-seeking by pregnant women during the COVID-19 pandemic. Methods: We performed a systematic review and meta-analysis of studies of the effects of the pandemic on provision of, access to and attendance at maternity services (CRD42020211753). We searched MEDLINE and Embase in accordance with PRISMA guidelines from January 1st, 2020 to April 17th 2021 for controlled observational studies and research letters reporting primary data comparing maternity healthcare-seeking and healthcare delivery during compared to before the COVID-19 pandemic. Case reports and series, systematic literature reviews, and pre-print studies were excluded. Meta-analysis was performed on comparable outcomes that were reported in two or more studies. Data were combined using random-effects meta-analysis, using risk ratios (RR) or incidence rate ratios (IRR) with 95% confidence intervals (CI). Findings: Of 4743 citations identified, 56 were included in the systematic review, and 21 in the meta-analysis. We identified a significant decrease in the number of antenatal clinic visits (IRR 0614, 95% CI 0486–0776, P <00001, I 2 =54.6%) and unscheduled care visits (IRR 0741, 95% CI 0602–0911, P = 00046, I 2 =00%) per week, and an increase in virtual or remote antenatal care (IRR 4656 95% CI 7762–2794, P <00001, I 2 =90.6%) and hospitalisation of unscheduled attendees (RR 1214, 95% CI 1118–1319, P <00001, I 2 =00%). There was a decrease in the use of GA for category 1 Caesarean sections (CS) (RR 0529, 95% CI 0407–0690, P <00001, I 2 =00%). There was no significant change in intrapartum epidural use ( P = 00896) or the use of GA for elective CS ( P = 079) Interpretation: Reduced maternity healthcare-seeking and healthcare provision during the COVID-19 pandemic has been global, and must be considered as potentially contributing to worsening of pregnancy outcomes observed during the pandemic.